Colonial Roots of the Contemporary Economic Crisis in Subsaharan Africa (SSA): The Case of Nigeria and Tanzania - Ishamali, Isaac; Adie, Clement Undiandeye (Universitas PGRI Madiun, 2024)
Tanzania is a low-income oil-importing developing country, with characteristics that typify the vulnerability of a Third World economy, with external debt payment crisis. Nigeria on the other hand, is a mineral-rich oil-exporting country also enmeshed in debt crisis. Sadly, Nigeria has been the region’s largest borrower. Both countries have different economic development strategies. While Tanzania with initial socialist bent, capitulated to the conditionalities of multilateral agencies, Nigeria on the other hand followed the path of a mixed economy and later reverted to the capitalist economic mode. This discourse examines the colonial roots of the economic crisis in both Nigeria and Tanzania. The study also x-rays the impacts of British colonial administration on Nigeria and Tanzania, and the political and economic systems that evolved in these colonies. The work found out that the imposition of indirect rule, which meant the superimposition of the colonial method of government on the various indigenous emirates, kingdoms, and tribal chieftaincies in Nigeria and Tanzania was for economic exploitation. The work submits that the underlying motive of colonialism was to ensure the effective and unchallenged exploitation of the colonies for the benefit of British capitalists, and the indirect rule system was intended as the best way to accomplish this end. This exploitation has however continued unabetted into the present-day neo-colonial exploitation aided by both Nigerian and Tanzanian collaborators.